2019
DOI: 10.1515/jogs-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Application of GNSS derived precipitable water vapour prediction in West Africa

Abstract: Atmospheric water vapour, a major component in weather systems serves as the main source for precipitation, provides latent heat which helps maintain the earth’s energy balance and a major parameter in Numerical Weather Prediction (NWP) models. An observational technique based on the Global Navigation Satellite System (GNSS) has made it possible to easily retrieve Precipitable Water (PW) at station’s antenna position with very high spatial and temporal variabilities. GNSS techniques are superior to ground-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Similar findings have also been obtained by Ahmadi and Rodehutscord (2017) and Parveen et al (2016Parveen et al ( , 2017. Furthermore, the performance of the QR model over the MLR model is also consistent with the study carried out by Acheampong and Obeng (2019). In the study, the authors estimated the amount of PWV over four selected IGS ground stations in West Africa using QR, MLR, and exponential regression (ER) models.…”
Section: Groups Pairsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar findings have also been obtained by Ahmadi and Rodehutscord (2017) and Parveen et al (2016Parveen et al ( , 2017. Furthermore, the performance of the QR model over the MLR model is also consistent with the study carried out by Acheampong and Obeng (2019). In the study, the authors estimated the amount of PWV over four selected IGS ground stations in West Africa using QR, MLR, and exponential regression (ER) models.…”
Section: Groups Pairsupporting
confidence: 83%
“…Moreover, if the under-studied IGS tracking stations' ZTD data are inaccessible or absent, the best prediction model can as well be utilized as an alternative model to predict the missing ZTD values as a means of improving continuous data availability at the stations. These models were selected following Clements et al (2005), Sayegh et al ( 2014)), Parveen et al (2016Parveen et al ( , 2017Parveen et al ( , 2020, Acheampong and Obeng (2019)), and Zhang et al (2019), as these models have been commonly used in other areas of study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation of the linear regressions between the GPS PWV and the TCWV exhibited high coefficients of determination. The high coefficients of determination of the empirical relation connecting the PWV and TCWV were also reported by Acheampong and Obeng (2019).…”
Section: Discussionmentioning
confidence: 71%
“…e study demonstrated that PWV can be obtained with high precision from GNSS signals in Ghana. Additionally, the authors in [30] studied the application of prediction models (regression and time-series) for predicting GNSS-PWV over four IGS stations in West Africa. e study reported the quadratic and autoregression models as the most appropriate regression and time-series models, respectively, for the prediction of PWV in West Africa.…”
Section: Introductionmentioning
confidence: 99%